A Proactive Strategy For Attracting Women Into Engineering - Gilbride, Kimberley A.; Kennedy, Diane C.; Waalen, Judith K.; Zywno, Malgorzata (Canadian Journal of Counselling and Psychotherapy, 2007)
In 1991, the Women in Engineering (WIE) Committee at Ryerson Polytechnic University initiated the Discover Engineering Summer Camp. The objectives of the program were to educate young women about the challenges and rewards of engineering, to show that engineering is a viable profession to consider, and to motivate women to choose engineering. Eighty-three percent of the 1996 camp participants said that they found the camp experience to be very beneficial, while 76% said that it had made a big difference to their awareness of what engineering was all about. Follow-up surveys from previous camp sessions found that approximately 60% of the young women who attended the Discover Engineering camp went on to pursue engineering and cited the camp as a key factor in their decision.